2015
DOI: 10.1080/02763869.2015.986805
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Loop on Nursing Library Instruction: Using Student Performance to Improve Outcomes

Abstract: Two librarians analyzed nursing students' performance on an information literacy assignment to determine how they could change their instruction to better assist the students in comprehending the material. After identifying major areas of difficulty, including the use of search techniques, they revised both the instruction and the assignment, closing the loop by utilizing their assessment data. Next, they analyzed those results to evaluate the effectiveness of their changes and to make further improvements, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The average score of first-year students on the proprietary pretest of our one-credit information literacy class is 67 per cent, which equates to a "D," or below average, indicating students are ill-prepared for college from an information literacy perspective. This finding corroborates the literature, which consistently indicates issues with the transition from high school to college, and the transition from college into the professional world (Farmer, 2014;Head et al, 2013;Moreton and Conklin, 2015;Winward, 2011). Given the information literacy deficiencies documented in the literature, this information literacy pipeline clearly warrants a second look.…”
Section: Introductionsupporting
confidence: 90%
“…The average score of first-year students on the proprietary pretest of our one-credit information literacy class is 67 per cent, which equates to a "D," or below average, indicating students are ill-prepared for college from an information literacy perspective. This finding corroborates the literature, which consistently indicates issues with the transition from high school to college, and the transition from college into the professional world (Farmer, 2014;Head et al, 2013;Moreton and Conklin, 2015;Winward, 2011). Given the information literacy deficiencies documented in the literature, this information literacy pipeline clearly warrants a second look.…”
Section: Introductionsupporting
confidence: 90%
“…Information literacy is being taught to nursing students with varying levels of success. While information literacy is important, it is also difficult to teach and assess effectively, and at times outcomes are only moderately improved (Farrell, Goosney, & Hutchens, 2013;Moreton & Conklin, 2015). According to a survey of instruction librarians, information literacy programs in higher education are often limited to first year instruction, although disciplinespecific instruction for undergraduates is also available (Julien, Gross, & Latham, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After duplicates, theses, and book reviews were removed, 62 articles remained and were checked for relevance. Four articles (Kavšek, Peklaj, & Žugelj, 2016;Lin, 2015;Moreton & Conklin, 2015;Sego & Stuart, 2016) were retrieved in full for further consideration. The study by Kavšek et al (2016) was found to be relevant to the review criteria; however, whilst the study used a control group, it was not randomized.…”
Section: Limitationsmentioning
confidence: 99%